2014
DOI: 10.1016/j.envint.2014.04.009
|View full text |Cite|
|
Sign up to set email alerts
|

Child exposure to indoor and outdoor air pollutants in schools in Barcelona, Spain

Abstract: Proximity to road traffic involves higher health risks because of atmospheric pollutants. In addition to outdoor air, indoor air quality contributes to overall exposure. In the framework of the BREATHE study, indoor and outdoor air pollution was assessed in 39 schools in Barcelona. The study quantifies indoor and outdoor air quality during school hours of the BREATHE schools. High levels of fine particles (PM2.5), nitrogen dioxide (NO2), equivalent black carbon (EBC), ultrafine particle (UFP) number concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
163
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(186 citation statements)
references
References 69 publications
17
163
4
2
Order By: Relevance
“…In comparison with a study conducted in 37 classrooms in Canada (Weichenthal et al, 2008), UFP in Portuguese schools were approximately 1.6-to 1.9-fold higher. In contrast, studies on UFP in 39 primary schools in Spain Rivas et al, 2014), 7 primary schools in Greece (Diapouli et al, 2007), and 2 primary schools in Italy (Buonanno et al, 2013b) reported 1.2-to 3.5-fold higher values of UFP. Similarly, studies from other non-European countries such as in California (Mullen et al, 2011), Australia (Morawska et al, 2009), and South Korea (Kim et al, 2011) noted considerably higher levels of UFP than the findings obtained in the cur-rent investigation.…”
Section: Discussionmentioning
confidence: 84%
“…In comparison with a study conducted in 37 classrooms in Canada (Weichenthal et al, 2008), UFP in Portuguese schools were approximately 1.6-to 1.9-fold higher. In contrast, studies on UFP in 39 primary schools in Spain Rivas et al, 2014), 7 primary schools in Greece (Diapouli et al, 2007), and 2 primary schools in Italy (Buonanno et al, 2013b) reported 1.2-to 3.5-fold higher values of UFP. Similarly, studies from other non-European countries such as in California (Mullen et al, 2011), Australia (Morawska et al, 2009), and South Korea (Kim et al, 2011) noted considerably higher levels of UFP than the findings obtained in the cur-rent investigation.…”
Section: Discussionmentioning
confidence: 84%
“…In working environments, PM size distribution, concentrations, and chemical properties are even more site-specific than in residential ones as these depend on the used materials, productive methods, and working typologies. Extensive literature on school environments, partially for assessing children's exposure (i.e., the tendency for health impairments, and the large percentage of daytime spent in those spaces) and as a major working sector for the number of employees, is found [14,[33][34][35].…”
Section: Brief Summary Of the Main Characteristics Of Pm In Indoor Anmentioning
confidence: 99%
“…Among them, Fe strongly dominates in both indoor and outdoor air (81% and 82% respectively), followed by Zn (12% both indoors and outdoors) and the other metals analyzed, with contribution lower than 3%, indicating the similar elemental consistency of indoor and outdoor particles. Fe is classified among mineral components, Cu among traffic-related components (brake pad abrasion tracers), Ni among heavy fuel-oil combustion components (mostly from shipping emissions) and Cd, Zn, Cr and Pb among industrial elements (Rivas et al, 2014). Among the metals studied, Ni and Cd are regulated through WHO guidelines (WHO, 2000) with a maximum value of 1000 ng m -3 for Ni and 5.0 ng m -3 for Cd.…”
Section: Metalsmentioning
confidence: 99%